Patient-reported experience of dry eye management: An international multicentre survey. Issue 1 (February 2022) - Bilkhu, Paramdeep; Sivardeen, Zimar; Chen, Connie; Craig, Jennifer P.; Mann, Kylie; Wang, Michael T.M.; Jivraj, Saleel; Mohamed-Noriega, Karim; Charles-Cantú, David E.; Wolffsohn, James S.
Abstract: Purpose: To explore the journey taken by patients in a range of different countries to manage their dry eye symptoms. Method: Members of the general public who responded positively to the question "Do your eyes ever feel dry?" completed a questionnaire describing their demographics, the impact of their symptomology, the advice they have received and the management options they have tried. The Ocular Surface Disease Index (OSDI) questionnaire was also completed. Results: A total of 916 individuals (Canada = 235, Mexico = 127, New Zealand = 157, Taiwan = 246, UK = 151) of similar age distribution (median 38 years, IQR: 27–50) completed the survey. The reported duration of symptoms was longest in Canada (median 4 years, range 2–10) and least in Taiwan (2 years, range 1–3; p < 0.001), and similar trends were observed for symptom severity (p = 0.001). However, there was no statistically significant difference between countries with respect to the impact of symptoms on quality of life (median 3/10; p = 0.08). Less than half of the individuals in any country had consulted with a health professional. About half had tried a treatment for their dry eye symptoms, with artificial tears being the most common treatment, followed by warm compresses, and both therapies were rated as reasonably effective (median 5−7/10). Conclusion: Many people with dry eye symptoms are not consulting health care professionals who can confirm the diagnosis, exclude differential diagnoses, and offer a wide range of treatments targeted at the dry eye subtype.